2024
DOI: 10.7759/cureus.51447
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Dry Eye Symptoms and Objective Ocular Surface Signs in a Civil Air Crew Population: A Cross-Sectional Study

Anna Fachinetti,
Edoardo Marelli,
Paola Velati
et al.

Abstract: Background Aviation professionals are often exposed to conditions such as low cabin air pressure, reduced humidity, and prolonged artificial lighting, which may predispose them to dry eye disease (DED). We therefore designed a cross-sectional study with three primary objectives. Our first aim was to determine the prevalence of subjective dry eye symptoms among civil flight personnel. To achieve this, we administered the Standard Patient Evaluation of Eye Dryness (SPEED) questionnaire. Second, we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Although some authors were unable to detect UV-A or UV-B radiation (wavelength: 280-315 nm) in airplane cabins or cockpits [19], there is increasing evidence that pilots carry genomic signatures consistent with UV-induced DNA damage [20,21]. This observation is further strengthened by occupational health studies showing that this professional category is at increased risk of UV-related disorders, including skin cancer [22,23], nuclear cataract [24], and dry eye disease [25]. Remarkably, a meta-analysis by Sanlorenzo et al [23] revealed that pilots have approximately twice the incidence of malignant melanoma compared to the general population.…”
Section: Increased Ultraviolet Radiation Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Although some authors were unable to detect UV-A or UV-B radiation (wavelength: 280-315 nm) in airplane cabins or cockpits [19], there is increasing evidence that pilots carry genomic signatures consistent with UV-induced DNA damage [20,21]. This observation is further strengthened by occupational health studies showing that this professional category is at increased risk of UV-related disorders, including skin cancer [22,23], nuclear cataract [24], and dry eye disease [25]. Remarkably, a meta-analysis by Sanlorenzo et al [23] revealed that pilots have approximately twice the incidence of malignant melanoma compared to the general population.…”
Section: Increased Ultraviolet Radiation Exposurementioning
confidence: 99%
“…UV radiation exposure can also result in increased oxidative stress and inflammation on the ocular surface, which are underlying mechanisms in the pathogenesis of dry eye disease [26]. This condition often manifests symptomatically with feelings of irritation, grittiness, or visual disturbances but can also occur asymptomatically, including among aircrew personnel [25]. In the context of climate change, the health hazards posed by UV radiation are becoming a more pressing issue for aviation workers due to the thinning of the stratospheric ozone layer [27].…”
Section: Increased Ultraviolet Radiation Exposurementioning
confidence: 99%